Liver Tissue Examination of Mice Using 10% BNF Fixation For 6 Hours And 16 Hours - Octary, Neike; Sari, Indah; Aristoteles (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The fixation process is the first stage in the manufacture of histopathological preparations which aims to preserve the tissue and harden the tissue, so that the tissue to be observed does not change in shape or size. BNF fixation solution (Neutral Buffer Formalin) 10% has been used as a routine fixative and It has been be the gold standard in histology laboratories for decades. The material used in this study was a 10% BNF solution because it is easier to use and it can be used to preserve tissue for a long period of time. This study aims to determine the differences in the microscopic results of the liver tissue of mice (Mus musculus) fixed with 10% BNF for 6 hours and 16 hours. This type of research is descriptive analytic. The research was carried out at the Barokah Laboratory/ dr.Mezfi Unita on 04-05 March 2022 with a total sample of 20 samples of mice liver tissue (Mus musculus). The results of the study on 10% BNF fixation for 6 hours and 16 hours showed that the average results were not good. The conclusion from the results of the study that there was no difference in the microscopic results of liver tissue that were fixed with 10% BNF for 6 hours and 16 hours using Hematorylin-Eosin staining. 10% BNF fixation with a time of 6 hours and 16 hours can be used as an alternative in histopathological examination in the short term and long term.